Appraisals of psychotic experiences: an experimental investigation of symptomatic, remitted and non-need-for-care individuals. Issue 6 (25th January 2016) - Underwood, R.; Kumari, V.; Peters, E.
Abstract : Background: Appraisals are suggested to play a determining role in the clinical outcome of psychotic experiences (PEs). We used experimental tasks that mimic PEs to investigate appraisals in individuals with PEs with and without a 'need-for-clinical-care', and psychosis patients whose symptoms have remitted. We predicted that patients would appraise the tasks as threatening regardless of current symptom level, while non-clinical and control groups would appraise them as non-threatening. Method: Appraisals following three anomalous experiences-inducing tasks [Telepath, Cards task, Virtual acoustic space paradigm (VASP)] were examined in 71 individuals: symptomatic ( n = 18) and remitted ( n = 16) psychosis patients; non-clinical group with PEs ( n = 16); controls without PEs ( n = 21). Results: As predicted, symptomatic patients endorsed more threatening appraisals for all tasks than non-clinical and control groups, who did not differ from each other. However, remitted patients were less likely to endorse threatening appraisals of the Cards and Telepath than their symptomatic counterparts, although they did not differ in global ratings of how striking, threatening and distressing they found the tasks. Moreover, remitted participants endorsed more threatening appraisals of the Telepath and VASP than non-clinical participants, and of the VASP than controls. Remitted participants also rated all three tasks as globally more threatening than the non-clinical group and controls. Conclusions: Clinical outcome may not necessarily be driven by the presence of symptoms, with threatening appraisals of PEs representing a key factor. The remitted group's intermediate appraisal scores imply that the relationship between appraisal and clinical outcome is not straightforward, and potential mediating factors need to be determined.